2008
DOI: 10.1242/jeb.013664
|View full text |Cite
|
Sign up to set email alerts
|

Larvae of the fall webworm, Hyphantria cunea, inhibit cyanogenesis in Prunus serotina

Abstract: SUMMARYThe larvae of the fall webworm, Hyphantria cunea (Dru.), though vulnerable to cyanide poisoning, consume the cyanogenic leaves of black cherry, Prunus serotina, without apparent harm. The cyanide contents of leaves, defensive regurgitant, the bolus, and frass were assayed by ion chromatography to determine the fate of the toxin in the caterpillar. Leaves collected in September, when the caterpillars were feeding, contained 1592±276·p.p.m. cyanide. Samples of dried frass obtained from caterpillars fed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…A similar inhibition of plant cyanogenesis by a highly alkaline midgut pH has only been reported in a few cases such as the ugly nest caterpillar or the fall webworm larva feeding on cherry [36], [37]. Highly alkaline conditions in the insect midgut may also inhibit plant β-glucosidases known from other two-component plant defence systems.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A similar inhibition of plant cyanogenesis by a highly alkaline midgut pH has only been reported in a few cases such as the ugly nest caterpillar or the fall webworm larva feeding on cherry [36], [37]. Highly alkaline conditions in the insect midgut may also inhibit plant β-glucosidases known from other two-component plant defence systems.…”
Section: Discussionmentioning
confidence: 67%
“…This percentage is lower than found in other insect herbivore species feeding on cyanogenic plant material. For example, feeding of the lepidopteran ugly nest caterpillar ( Archips cerasivoranus ) and the fall webworm ( Hyphantria cunea ) on cherry ( Prunus ) species, results in emission of more than 2.5% and 10% of the total leaf HCN potential, respectively [36], [37]. Feeding of the orthopteran desert locust ( Schistocerca gregaria ) on lima beans ( Phaseolus lunatus ) results in emission between ∼ 2.5% and 15% of the HCN present in consumed leaf material, depending of the cyanogenic capacity and potential of the plant cultivar [38].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in pH may affect enzymatic reactions by changing the charge of certain amino acids, affecting protein conformation and their catalysis (Johnson & Felton, ; Harrison, ). Whereas the haemolymph of insects is mostly neutral with pH ranging from 6.4 to 7.5, the pH of the midgut lumen varies from a strongly acidic pH 3.1 to extremely alkaline pH 12.4 among different insect orders (Berenbaum, ; Dow, ; Schultz & Lechowicz, ; Johnson & Felton, ; Appel & Joern, ; Harrison, ; Cristofoletti et al , ; Fitzgerald, ; Terra & Ferreira, ). Regulation of midgut pH mainly involves H + V‐ATPases that are located in the apical membrane of goblet cells in the midgut (Wieczorek et al , ).…”
Section: From Feeding To Digestion: Targets For Insect Herbivore Adapmentioning
confidence: 99%
“…Although caterpillars of the generalist fall webworm Hyphantria cunea (Lepidoptera, Arctiidae) are vulnerable to hydrogen cyanide, they can feed on leaves of black cherry ( Prunus serotina , Rosaceae) containing cyanogenic glucosides without any adverse effects (Fitzgerald, ). A high alkaline midgut lumen at pH 11 was shown to prevent the hydrolysis of cyanogenic glucosides into toxic hydrogen cyanide during passage of the plant parts through the gut (Fitzgerald, ), most likely due to inhibition of plant β‐glucosidases. A direct link between an alkaline midgut and reduced plant β‐glucosidase activity towards benzoxazinoid glucosides was shown in the generalist fall armyworm feeding on maize containing DIMBOA‐glucosides (Dutartre et al , ).…”
Section: From Feeding To Digestion: Targets For Insect Herbivore Adapmentioning
confidence: 99%
“…Any residual β -glucosidase activity left on the leaf edges or in the leaf pieces will be inhibited by the alkaline midgut pH. Larvae of the fall webworm (Hyphantria cunea) also has an alkaline midgut environment which allow them to feed on black cherries without trigging their cyanogenic potential (Fitzgerald, 2008). Amelot et al, (2006) demonstrated that larvae of Heliconius erato released less hydrogen cyanide than Spodoptera furgiperda when feeding on Passiflora capsularis (5.8 fold difference).…”
Section: Heliconius Larvae Avoid Degradation Of Cnglcs During Feedingmentioning
confidence: 99%